A privacy‐preserving group authentication protocol for machine‐type communication in LTE/LTE‐A networks. Issue 13 (12th February 2016) - Fu, Anmin; Song, Jianye; Li, Shuai; Zhang, Gongxuan; Zhang, Yuqing
Abstract: Machine‐type communication (MTC) is a very important application of the Internet of things. It has a vast market and application scenarios. However, supporting a large number of low‐power devices transmission is an important issue in long‐term evolution/long‐term evolution advanced (LTE/LTE‐A) networks. Specifically, when a large number of machine‐type communication devices (MTCDs) with low‐power consumption requirements simultaneously request access to the LTE/LTE‐A networks, each MTCD needs an independent complete access authentication process with core network, which may cause a serious signaling congestion in the core network. To solve this problem, in this paper, we propose a novel group authentication protocol with privacy‐preserving for MTC in the LTE/LTE‐A networks. The proposed protocol cannot only simultaneously authenticate a group of MTCDs and minimize the signaling overhead but also provide robust privacy‐preserving for each MTCD (including anonymity, unlinkability, and traceability). In particular, our scheme can avoid denial of service attack by filtering some illegal devices in the first four procedures of the mutual authentication. Moreover, our scheme fulfills all the security requirements of the MTC in LTE/LTE‐A networks. In addition, the formal verification by the ProVerif tool shows that the proposed scheme is secure against various malicious attacks, and the performance evaluation indicates that it achieves outstanding results in terms of signaling and computation overhead. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Supporting a large number of low‐power devices transmissions is an important issue in long‐term evolution/long‐term evolution advanced networks. In this paper, we proposed a novel group authentication scheme, which can simultaneously authenticate a group of machine‐type communication devices by adopting aggregate message authentication code and providing robust privacy‐preserving including user anonymity, unlinkability, and traceability. Theoretical analysis and simulation results show that our scheme can fulfill more security requirements and have a good performance.